Foot Care Behavior Among People With Type 2 Diabetes Mellitus: Overview and Sociodemographic Factors Impact - Rondhianto Rondhianto; Nur Widayati; Sinta Qur'aini (KHD-Production, 2023)
Foot care behavior is essential to prevent the risk of diabetic foot ulcers among people with type 2 diabetes mellitus (T2DM). The sociodemographic predisposing factors had determined mainly behavior. The study aimed to analyze sociodemographic factors' effect on foot care behavior in people with T2DM. This study was an analytical observational study with a cross-sectional design. The sample size was 130 respondents, with multistage random sampling. The instruments used were a questionnaire. The results showed that most of the respondents were 56-65 years (45.38%), women (62.31%), married (86.15%), basic education (46.15%) and income level were less than the district minimum wage (56.92%), Madurese (54.62%), nuclear family type (46.15%), and had foot care behavior in the good category (71.54%). Income level was the sociodemographic factor significantly affecting foot care behavior (p=0.019). Respondents with low-income levels (less than regency minimum wage) showed poor foot care behavior. At the same time, other sociodemographic factors, such as age, gender, marital status, education level, ethnicity, and family type, did not affect foot care behavior (p-value > α = 0.05). The higher the income level, the better the foot care behavior. Providing diabetes education to increase awareness of diabetic patients about foot care is essential to paying attention to sociodemographic conditions, especially income levels. Good foot care behavior can reduce the risk of diabetic foot ulcers, minimize morbidity, and improve the quality of life of people with T2DM.